(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Acute appendicitis is the most common cause of surgical acute abdomen and appendicectomy is the most commonly done surgery. Accurate preoperative diagnosis can reduce negative appendicectomy rate. Objective: To evaluate the diagnostic accuracy of C-reactive protein (CRP), total leucocyte count (TLC) and neutrophil count in patients operated after clinical diagnosis of acute appendicitis. Materials and Methods: This cross-sectional observational study was conducted among 100 patients at Combined Military Hospital, Dhaka from August 2012 to January 2013. Serum CRP level was measured by latex agglutination method which is a qualitative test and level of 6 mg / L was considered positive. TLC and neutrophil count were estimated by processing blood sample through automated haematology analyzer. TLC level of 10.5 x 109/L and differential count of neutrophil more than 75% were considered elevated. Results: Out of 100 cases the mean age of the patients was 21.7 years and 65 patients were male and 35 patients were female with male to female ratio 1.85:1. Majority cases (54%) were in the age group of 11-20 years. Clinical diagnosis was correct in 93% cases and negative appendicectomy rate was 07% (p<0.001). Appendix was found mostly inflamed (83%) and gangrenous (10%). CRP was highly sensitive (84.9%) and specific (85.7%) with diagnostic accuracy of 85%. TLC was also found equally sensitive and specific with diagnostic accuracy of 83%. Overall diagnostic accuracy of neutrophil was 76%. Conclusion: Diagnosis of acute appendicitis is essentially clinical supported by simple laboratory investigations like TLC and neutrophill count. Elevated levels of CRP, TLC and neutrophill count are helpful in confirming a suspected diagnosis of acute appendicitis. Appendicitis is very unlikely if the CRP, TLC and neutrophill counts are normal. JAFMC Bangladesh. Vol 17, No 1 (June) 2021: 26-29